Invitación a la conferencia "Génesis de la bandera puertorriqueña" por Roberto H. Todd - Todd, Roberto H. (My University, 1937)
Invitación a la conferencia "Génesis de la bandera puertorriqueña" por Roberto H. Todd.
Keywords: Flags--Puerto Rico.; Bandera--Puerto Rico.